How does distraction osteogenesis maxillary expansion (DOME) reduce severity of obstructive sleep apnea? - Iwasaki, Tomonori; Yoon, Audrey; Guilleminault, Christian; Yamasaki, Youichi; Liu, Stanley Yung (Sleep & breathing, 2020)
Objective Distraction osteogenesis maxillary expansion (DOME) is a reliable method to expand the nasal floor and hard palatal vault in adults with obstructive sleep apnea (OSA). DOME results in a reduction in the apnea-hypopnea index (AHI) and subjective report of improved nasal breathing. Using rhinomanometry augmented computational fluid dynamic (CFD) modeling, we propose a mechanism of how DOME reduces upper airway pharyngeal collapse in adults with OSA. Material and method A retrospective cohort with 20 subjects and mean age of 29.6 ± 8 years who completed DOME at Stanford University from September 2014 to April 2016. Subjects were included if polysomnography, airway morphology, and rhinomanometry were available for use. From the CBCT data, 3D nasal and pharyngeal airway model were generated. Numeric CFD simulation of the airway models were analyzed under the following conditions: (1) the volume of air was flowing at a velocity of 300 cm 3 /s, (2) the wall surface was not slippery, and (3) the simulations were repeated 1000 times to calculate mean values. Statistical analyses using SPSS v24 software included paired t tests, nonparametric Wilcoxon rank test, Friedman test with Bonferroni correction, and Spearman’s correlation coefficients ( p < 0.05). Results Mean AHI improved from 17.8 ± 17.6 to 7.8 ± 7.1 events per hour ( p < 0.001). Mean lowest oxygen saturation improved from 88.2 ± 7.2 to 90.9 ± 4.2% ( p < 0.05). Mean airflow velocity within the nasal airway decreased from 15.6 ± 7.3 to 7.4 ± 2.1 m/s ( p < 0.001) after DOME. Mean negative pressure of the nasal airway, retropalatal airway, oropharyngeal airway, and hypopharyngeal airway is reduced from − 158.4 ± 115.3 to − 48.6 ± 28.7 Pa, from − 174.8 ± 119.9 to − 52.5 ± 31.3 Pa, from − 177.0 ± 118.4 to − 54.9 ± 31.8 Pa and from − 177.9 ± 117.9 to − 56.9 ± 32.1 Pa ( p < 0.001), respectively. AHI positively correlated with nasal flow velocity ( p < 0.05) and negatively correlated with pharyngeal airway pressure ( p < 0.05). ODI was positively correlated with nasal velocity ( p < 0.05) and negatively correlated with nasal airway pressure ( p < 0.05), retropalatal airway pressure ( p < 0.001), oropharyngeal airway pressure ( p < 0.001), and hypopharyngeal airway pressure ( p < 0.05). Conclusion Anatomic expansion of the nasal floor with widening of the hard palatal vault from DOME is associated with reduction of nasal airflow velocity and downstream reduction of negative pressure in the pharyngeal airway. This dynamic interaction correlates with a reduction in the apnea-hypopnea index (AHI) and Oxygen Desaturation Index (ODI).